2022
DOI: 10.3389/fpls.2022.984269
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive meta-QTL analysis for yield-related traits of durum wheat (Triticum turgidum L. var. durum) grown under different water regimes

Abstract: Abiotic stress strongly affects yield-related traits in durum wheat, in particular drought is one of the main environmental factors that have effect on grain yield and plant architecture. In order to obtain new genotypes well adapted to stress conditions, the highest number of desirable traits needs to be combined in the same genotype. In this context, hundreds of quantitative trait loci (QTL) have been identified for yield-related traits in different genetic backgrounds and environments. Meta-QTL (MQTL) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 86 publications
(88 reference statements)
5
14
0
Order By: Relevance
“…Climatic data are highly correlated with the adaptation of the crop. As it is shown by different authors [ 22 , 29 ], PCoA using molecular data followed the climatic classification reported by these authors when genotypes were grouped by their country of origin. However, the high level of admixture and genetic exchange in the Mediterranean landraces according to Rufo et al [ 12 ] revealed an unclear pattern when comparing PCoA using structure or climatic data.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Climatic data are highly correlated with the adaptation of the crop. As it is shown by different authors [ 22 , 29 ], PCoA using molecular data followed the climatic classification reported by these authors when genotypes were grouped by their country of origin. However, the high level of admixture and genetic exchange in the Mediterranean landraces according to Rufo et al [ 12 ] revealed an unclear pattern when comparing PCoA using structure or climatic data.…”
Section: Discussionmentioning
confidence: 61%
“…The dissection of genetic architecture for phenology in Mediterranean wheat landraces revealed the presence of 26 QTL hotspots (57%) with significant associations. According to the position of functional genes described by Liu et al [ 29 ], major genes affecting photoperiod sensitivity and vernalization were in QTL hotspots 2A.1 ( Ppd-A1 ) and 5A.3 ( Vrn-A1 ), respectively. However, no MTAs were found in the homologous regions corresponding to the Ppd and Vrn genes on chromosomes 2B and 2D, and 5B and 5D, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The main approach to augmenting crop yield is to increase the number and the weight of grains [ 64 ]. In this sense, the traits that have been studied to increase seed yield in common bean are pods per plant, seeds per plant, seed weight, and pod harvest index [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The best model of MQTLs was chosen according to Akaike Information Criterion (AIC), corrected Akaike Information Criterion (AICc and AIC3), Bayesian Information Criterion (BIC), and Average Weight of Evidence (AWE) criteria. The number of MQTLs present on each chromosome was determined when values of the model selection criteria were the lowest in at least three of the five models [ 64 ]. Given that MQTL analysis is a method to combine QTL results from different independent analyses, a MQTL with a confidence interval of 95% was reported when it contained QTL from at least two different studies [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Polyploidy, in fact, on the one hand confers a high degree of plasticity to the organism, on the other hand it makes genetic analysis more difficult for scientists and breeders aimed at dissecting the molecular basis underlying quantitative and qualitative traits ( Dubcovsky et al, 2007 ; Bevan et al, 2017 ). So far, most efforts to understand the genetic basis of key traits related to yield, grain quality and adaptability have been made through map-based cloning approaches (summarized by Colasuonno et al, 2021 ; Soriano et al, 2021 ; Arrigada et al, 2021 ). For example, genes involved in vernalization and photoperiod response ( Yan et al, 2003 , 2004 ; Díaz et al, 2012 ), grain protein content ( Uauy et al, 2006 ), grain quality ( Jin et al, 2018 ; Goel et al, 2019 ; Semagn et al, 2021 ) stem solidness ( Nilsen et al, 2020 ), male sterility ( Ni et al, 2017 ; Xia et al, 2017 ), and resistance to fungal diseases ( Fu et al, 2009 ) have been identified and cloned.…”
Section: Introductionmentioning
confidence: 99%